Effect of temperature on the vapour fraction of heavy crude oil in hydrodynamic cavitation Vortex reactor using CFD. (2021)
Hydrodynamic cavitation is a technology recently implemented for industry applications, such as water treatment, biofuel generation or upgrading of heavy crudes. Heavy crudes are characterised by their low API gravity and high viscosity, which results in higher extraction, transport, and refining costs, and a lower selling price due to their lower content of light fractions such as naphtha. Thus, hydrodynamic cavitation reactors are used to cavitate the crude oil and improve viscosity, and the efficiency is highly dependent on the operating parameters, such as inlet pressure, temperature, and percentage of a hydrogen donor. In this work, the effect of temperature on the fluid dynamics of the crude oil inside the Vortex HCR-Nano reactor is analysed, taking as a response variable the volume fraction of vapour. The CFD study was done using Ansys Fluent, with five different temperatures between 92◦F and 350◦F, 3D steady-state flow modelling for liquid-vapour multiphase fluid, with realisable k-ε turbulence model, and Schnerr-Sauer cavitation. Results show that the volume of vapour increases with temperature, up to a volume of 1.507 cm3, where its main contribution is due to the Vortex effect. Further research includes the behaviour of hydrodynamic cavitation with different crude oils and operating parameters.